A newborn with blood blisters. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
A 15-day-old boy was first observed due to the presence of blood blisters on the upper limbs and of serum, tense blister on the sacral region. Autoimmune bullous diseases, bullous pyoderma or burns were hypothesized.